Looking back, moving forward a review of group and team-based research (Research on managing groups and teams, 2012)
Foreword / Margaret A. Neale, Elizabeth A. Mannix -- Studying dynamics within groups / Laurie R. Weingart -- Leadership in small groups and teams : toward a theory of group leadership / Randall S. Peterson, Kawon Kim -- Micropolitics : a new model of status hierarchies in teams / Cameron Anderson, Jessica A. Kennedy -- The far-reaching effects of power : at the individual, dyadic, and group levels / Adam D. Galinsky, Eileen Y. Chou, Nir Halevy, Gerben A. Van Kleef -- The nature of collective reactions to potential transgressions / Peter H. Kim, Derek J. Harmon -- Managing conflict in groups and teams : conflict about conflict / Karen A. Jehn, Sonja Rispens, Sherry M.B. Thatcher -- Political correctness and group composition : a research agenda / Jennifer A. Chatman, Jack A. Goncalo, Jessica A. Kennedy, Michelle M. Duguid -- Delusions of homogeneity? : reinterpreting the effects of group diversity / Katherine W. Phillips, Evan P. Apfelbaum -- Challenges and opportunities for group learning and group learning researchers / Jonathan Kush, Courtney Williamson, Linda Argote -- Technology and teams : the next ten years / Terri L. Griffith -- Engaging groups and organizational decisions : a social dilemma perspective / Gregory B. Northcraft, Kevin W. Rockmann -- Time pressure, performance, and productivity / Don A. Moore, Elizabeth R. Tenney -- Toward better understanding of interaction dynamics in multicultural teams : a status perspective / Raphael Silberzahn, Ya-Ru Chen -- When identities, interests, and information collide : how subgroups create hidden profiles in teams / Jeffrey T. Polzer, Lisa B. Kwan -- Epilogue / Maggie Neale, Beta Mannix